Profile of Congenital Heart Disease in childhood - Shalini Hajela (International Journal of Medical Research and Review, 2014)
Introduction: Globally, the prevalence of congenital heart diseases is 3.7 to 17.5 per 1000 live births; in India, it is 2.25-5.2 per 1000 children. The profile of Congenital Heart Disease varies with the age group; Simple heart defects are common at all ages, whereas serious defects are seen in autopsy. This study aims to assess the clinical profile of Congenital Heart Disease.Materials and Methods: The study was conducted in Department of Pediatrics, Bundelkhand Medical College, Sagar, India. It was a prospective study of cases attending the pediatric outpatient and inpatient department, as described by inclusion criteria over a period of 1 year. 100 cases could be included. Clinical assessment, 2 D Echocardiography and Color Doppler were used for diagnosis.Results: A prevalence of 15.38 per 1000 patients was observed. The commonest acyanotic Congenital Heart Disease was Ventricular septal defect (29%), followed by Atrial septal defect (13%) and Patent ductus arteriosus (5%). The commonest Cyanotic Congenital Heart Disease was Tetralogy of Fallot (26%) followed by Transposition of Great Arteries (9%) and Total anomalous Pulmonary Venous Connection (4%). Most children with heart disease were diagnosed between 1-5 years of age, acyanotic heart disease presenting at a mean age of 11.5 months, cyanotic heart disease with decreased pulmonary blood flow at 10.5 months and cyanotic heart disease with increased pulmonary blood flow at 5 months.Conclusions: Heart diseases are a significant cause of morbidity and mortality in children. Early diagnosis and early referral for definitive surgery is necessary to improve their quality of life.